2015
DOI: 10.3390/en8020684
|View full text |Cite
|
Sign up to set email alerts
|

Energy, Exergy and Performance Analysis of Small-Scale Organic Rankine Cycle Systems for Electrical Power Generation Applicable in Rural Areas of Developing Countries

Abstract: This paper introduces the concept of installing a small-scale organic Rankine cycle system for the generation of electricity in remote areas of developing countries. The Organic Rankine Cycle Systems (ORC) system uses a commercial magnetically-coupled scroll expander, plate type heat exchangers and plunger type working fluid feed pump. The heat source for the ORC system can be solar energy. A series of laboratory tests were conducted to confirm the cycle efficiency and expander power output of the system. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…Exergetic efficiency is recommended for evaluation of lowtemperature power systems and comparison of their performance for different heat source temperature [38,39]. Exergetic efficiency expression depends on the heat source type and the application [40].…”
Section: Orc Engine E Exergy Analysismentioning
confidence: 99%
“…Exergetic efficiency is recommended for evaluation of lowtemperature power systems and comparison of their performance for different heat source temperature [38,39]. Exergetic efficiency expression depends on the heat source type and the application [40].…”
Section: Orc Engine E Exergy Analysismentioning
confidence: 99%
“…Kane et al [12] design a mini-hybrid solar power plant integrating solar collectors, ORC cycles and bio-diesel engine to confirm the operational characteristics of this hybrid system to meet the electricity, cooling and pumping needs for rural areas. Baral et al [13] tested a small-scale ORC unit with a commercial scroll expander and found that the unit has the capacity to produce 1.4 kW of electric power when the heat source was 120 °C. In a similar manner, Delgado and Lourdes [14] conducted a parametric study of the influence of the configuration of the solar ORC system for various working fluids in a desalination process to determine the minimum aperture area required to produce mechanical power output under different operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve these, exergetic analysis based on the second law of thermodynamics is required [24][25][26]. The exergetic analysis is necessary to understand the extent of irreversibility in each component process, identify…”
Section: Exergy Calculationsmentioning
confidence: 99%